2017
DOI: 10.1149/2.0871707jes
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Functional Copper Sulfide as Sulfur Carrier for High-Performance Lithium-Sulfur Batteries

Abstract: Copper sulfide/sulfur composite, containing highly dispersed CuS, Cu 2 S and sulfur, is obtained via a facile one-step reaction of copper chloride and sodium thiosulfate. Based on the total mass of composite, a high initial capacity of 782.4 mAh g −1 with high coulombic efficiency of 97.4% is obtained, and after 50 cycles, the discharge capacity can still be retained at 580.2 mAh g −1 . The excellent electrochemical performance can be attributed to the tri-functional copper sulfide in the composite, which is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A microporous carbon support with Cu nanoparticles has been tested as S host in a Li–S battery, which enabled to maintain a specific capacity of 600 mAh g −1 after 500 cycles in ether‐based electrolyte . X‐ray absorption spectroscopy (XAS) studies have indicated that the reaction between metallic Cu and polysulfides to generate Cu x S and the higher binding energies of Cu x S toward Li 2 S x , together improve S utilization in Li–S batteries …”
Section: Introductionmentioning
confidence: 99%
“…A microporous carbon support with Cu nanoparticles has been tested as S host in a Li–S battery, which enabled to maintain a specific capacity of 600 mAh g −1 after 500 cycles in ether‐based electrolyte . X‐ray absorption spectroscopy (XAS) studies have indicated that the reaction between metallic Cu and polysulfides to generate Cu x S and the higher binding energies of Cu x S toward Li 2 S x , together improve S utilization in Li–S batteries …”
Section: Introductionmentioning
confidence: 99%
“…The peak presented at 932.1 eV belongs to Cu + species in Cu‐N, or from Cu 2 S . And the high‐resolution S 2p XPS spectrum is shown in Figure i; the peaks located at 160.7 and 161.2 eV correspond to the SCu bond from the mixed‐phase of CuS and Cu 2 S and further explains the confinement of sulfur through chemical affects. The peaks at binding energies of 163.1, 164.3, and 167.8 eV are ascribed to S 2p 3/2 , S 2p 1/2 , and the sulfate species, respectively .…”
Section: Resultsmentioning
confidence: 96%
“…The content of sulfur in the Cu x S@NC/S‐F, Cu x S‐NC/S, and NC/S‐F composite estimated from TGA in N 2 is 80, 80, and 88.6 wt%, respectively (Figure S5b, Supporting Information). The second weight loss of 2.3 wt% between 310 and 440 °C is mainly attributed to the phase transformation of CuS to Cu 2 S and sulfur . Thus, the weight fraction of CuS and Cu 2 S in the Cu x S‐containing composites is calculated to be about 13.8 and 2.1 wt%, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations